Validity Publishing the Conformity of Space Use Activities (Kkpr) That Are Not in Accordance With the Spatial Plan - Siti Sundari; Rusdianto Sesung (Journal of Law, Politic and Humanities, 2025)
This research aims to determine the validity of issuing conformity in space utilization activities (KKPR) that are not in accordance with the spatial plan. The research method used is normative legal research.  The approach used to examine various laws and regulations related to the regulation of obligations for the issuance of KKPR in accordance with the Regional Spatial Plan. The results of the analysis show that the policy regarding the obligation to issue KKPR in accordance with the Regional Spatial Plan has been regulated and stipulated in the Legislative Regulations. This is a basic requirement for submitting a KKPR. Apart from that, this validity is based on several aspects including authority, suitability of procedures and substance. In the event that the KKPR has been issued in accordance with its authority and has gone through appropriate procedures, but there are deficiencies in substance, then it can be concluded that the published KKPR is invalid.